Description of Movement Pain Levels Sufferers of De Quervain Syndrome in Students of SMA Negeri 1 Gambut - Risma Rahmanita; Arfian Hamzah; Maulida Wijaya (UPPM Politeknik Unggulan Kalimantan, 2024)
De Quervain Syndrome is pain in the styloid process area distal to the radius bone caused by inflammation of the tendon covering of the abductor pollicis longus and extensor pollicis brevis muscles caused by repeated injury or overuse, and is characterized by a positive Finkelstein test. This study aims to describe the level of motion pain in sufferers of de quervain syndrome in students of SMA Negeri 1 Peat. This study used a quantitative research type with an analytic descriptive research design to determine the level of motion pain in those with De Quervain Syndrome using the Visual Analogue Scale (VAS), which is a measuring instrument for measuring pain intensity. The results showed that the most positive DQS was at the age of 16 years (67.46%), the most female sex (61.50%), the movement that experienced the most pain was the abduction movement of the thumb (81.74%), and based on the level of motion pain mostly at moderate pain level (66.26%).